Strain-Engineered MOSFETs - Maiti, C.K (CRC Press, 2012)
This book brings together new developments in the area of strain-engineered MOSFETs using high-mibility substrates such as SIGe, strained-Si, germanium-on-insulator and III-V semiconductors into a single text which will cover the materials aspects, principles, and design of advanced devices, their fabrication and applications. The book presents a full TCAD methodology for strain-engineering in Si CMOS technology involving data flow from process simulation to systematic process variability simulation and generation of SPICE process compact models for manufacturing for yield optimization.